Effect of Low Solvent Concentration on the Rheological Behavior of Zirconia Ceramic Suspension and the Mechanical Properties of Sintered Parts - Giovanna Rubo de Rezende; Ítalo Leite de Camargo; Carlos Alberto Fortulan (Materials Research)
Homogeneous and stable ceramic suspensions with high solids loading and low viscosity pose a significant challenge in vat photopolymerization additive manufacturing, once solid particles tend to increase viscosity. Instead, organic materials can contribute to decrease viscosity and post-sintering shrinkage. A base suspension was formulated using PEGDA along with dispersant DISPERBYK-111 (3 wt.% of the monomer powder), zirconia powder (40 vol.%), n-methyl-2-pyrrolidone (10% vol.), and a photoinitiator (2 wt.% of the monomer). The introduction of 10 vol.% solvent resulted in a 22.6% reduction in the suspension viscosity. The average post-sintering shrinkage measured 26.11% across all three dimensions. Sintered components exhibited an average density of 5.95 g/cm3 and an average flexural strength of 256 ± 49 MPa. Additionally, the parts demonstrated anisotropic tribological behavior, low porosity and low surface roughness for polished (Ra 0.032) and untreated (Ra 0.33) surfaces. It was concluded that incorporating minimal amount of solvent into ceramic suspensions does not adversely affect their rheological and mechanical properties, while ensuring satisfactory surface quality of the sintered components.